FTMSK online student support system (FOSS) / Karno Omar - Omar, Karno (Faculty of Computer and Mathematical Sciences, 2005)
The process of learning is a continuous process from the first day a child is born till the day he/she dies. Learning is done either formally or informally. Talking about higher education learning, students of today are blessed with the information communication technology (ICT) which can be incorporated in the learning process. Education institutes have adopted the technology to add up the variety of learning process. They have provided students as well as lecturers with a system which can help in the process. Most of this systems are known as student portals. This thesis looks at the process of developing an Internet based online student support known as FTMSK Online Student Support (FOSS) that will provide an opportunity to present Faculty of Information Technology and Quantitative Science (FTMSK)'s curriculum in an interactive manner using web technologies